Dieta de duas espécies de peixes da família Cichlidae (Actinopterygii – Perciformes) na região do aproveitamento elétrico de estreito: Rio Tocantins, Ma - Reis, Luis Rogério Godinho dos (2013)
The inclusion of artificial barriers in freshwater ecosystems can trigger ecological, economic and social processes, affecting them. The food plasticity is an adaptive feature to the new environment, it is expected that the food of fish species under modified atmospheres follows changes in nutrient availability in the environment. To evaluate whether among the different phases of construction of Estreito barrage, Tocantins River, MA there are differences in the dietary habits of the family Cichlidae, collecting expeditions were conducted from November 2009 to 2010, (river stage) and November 2010 to April 2011 (filling phase), with an average duration of 10 days per year. The food items of dominant cichlid were analyzed using frequency and volume index, combined in Alimentary Index(IAI). The Shannon index was used to evaluate the diversity of items and classification of trophic guild. Significant differences in amplitude niche between the river and filler phases were verified by testing Hutcheson. Among cichlids found in fishes and alga influences barrage area, Geophagus proximus and Cichla proximus piquiti were dominant, being examined 26 specimens of Geophagus proximus in river stage and 6 specimens in filling stage, with results suggesting an omnivorous diet, predominantly f item in river stage and insects item for filling phase. The Cichla piquiti were examined 28 specimens in river stage and 32 specimens during stage filling, suggesting a piscivorous diet in both phases of the barrage. The number of food categories ranged between 09, during river phase and 08 the filling phase to Ciclha piquiti and between 14 during river phase and 12 the filling phase to Geophagus proximus. The test of difference in niche amplitude between the two phases revealed a nonsignificant difference for Cichla piquiti and significant for Geophagus proximus. It is concluded that the change in the hydrological regime caused by different stages in construction of the Estreito barrage (river and filling) led to changes in dietary habits in only one of two species of fish of the Cichlidae family in the region. Cichla piquiti presented itself more specialized as to its feed, preserving the two phases of the barrage piscivorous habit as that Geophagus proximus proved to have a greater trophic plasticity, having a greater amount of food items and diversifying them, in the two phases of the barrage, but not diversifying its trophic guild.